Miniature schnauzers - Stone, Lynn M. (Vero Beach, FL : Rourke Publishing LLC, 2007)
Describes the Miniature schnauzer, where it came from, how big they can get, and how much they weigh.
Includes bibliographical references (p. 24) and index.
1.0-4.0.
Accelerated Reader
Keywords: Miniature schnauzer